2017
DOI: 10.1097/md.0000000000008289
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neutrophil-to-lymphocyte ratio and diabetic peripheral neuropathy in Type 2 diabetes mellitus

Abstract: To explore the relationship between neutrophil-to-lymphocyte ratio (NLR) and diabetic peripheral neuropathy (DPN) in type 2 diabetes mellitus.A total of 557 newly diagnosed Type 2 Diabetes Mellitus (T2DM) patients were recruited, including 397 T2DM patients without complication (DM group) as well as 160 T2DM patients complicated with DPN (DPN group). Student t test, Mann–Whitney U test, or χ2 test was applied to the data of the 2 groups, including the levels of neutrophils and lymphocytes as well as the NLR va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 47 publications
10
58
4
2
Order By: Relevance
“…For this purpose, the fasting blood glucose, lipid profile, complete blood count and total testosterone level that are requested by clinicians are among these tests (Burnett, ). Studies conducted on NLR and PLR values, which show the relation between systemic inflammation and many diseases in ED and aetiology, are increasing in the present literature (Furuncuoğlu et al, ; İdil Soylu et al, ; Meng et al, ; Tulgar et al, ; Varım et al, ; Xu et al, ). When we selected our study group, we included not only the pre‐treatment values, but also those who were asked for a CBC for any reason to determine the changes in the 1st month after PDE5i treatment, which is different from previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For this purpose, the fasting blood glucose, lipid profile, complete blood count and total testosterone level that are requested by clinicians are among these tests (Burnett, ). Studies conducted on NLR and PLR values, which show the relation between systemic inflammation and many diseases in ED and aetiology, are increasing in the present literature (Furuncuoğlu et al, ; İdil Soylu et al, ; Meng et al, ; Tulgar et al, ; Varım et al, ; Xu et al, ). When we selected our study group, we included not only the pre‐treatment values, but also those who were asked for a CBC for any reason to determine the changes in the 1st month after PDE5i treatment, which is different from previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…Xu et al conducted a study and compared 160 Type 2 DM patients with diabetic polyneuropathy (DPN) and 397 Type 2 DM patients without polyneuropathy and found that mean NLR value was higher at a significant level in DPN group (2.58 ± 0.50 vs. 2.18 ± 0.61, p < 0.001) and stated that it could be an independent risk factor ( p = 0.002, OR = 4.960, 95% CI = 1.843–13.349) (Xu et al, ). Horne et al conducted a study with 3,227 patients and found that NLR was an independent predictor of cardiovascular risk (HR 2.2, p < 0.001) (Horne et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies confirmed that the NLR is closely related to the risk of diabetes and diabetic complications . However, the predictive value of the NLR for the risk of diabetic nephropathy and kidney function decline is still not clear.…”
Section: Commentmentioning
confidence: 99%
“…Recent studies confirmed that the NLR is closely related to the risk of diabetes and diabetic complications. 2,7,8 However, the predictive value of the NLR for the risk of diabetic nephropathy and kidney function decline is still not clear. Based on a large-scale prospective study, we found that NLR was an independent predictive factor for kidney function decline among individuals with diabetes and prediabetes.…”
Section: Commentmentioning
confidence: 99%